Attitudes of patients with metastatic cancer towards research biopsies. Issue 3 (6th November 2017) - Robinson, Danielle H.; Churilov, Leonid; Lin, Nancy U.; Lim, Elgene; Seah, Davinia
Abstract: Aim: To evaluate the attitudes of patients with different cancers towards research biopsies outside a clinical trial. Methods: Patients with metastatic cancer completed a questionnaire that assessed patients' willingness to consider research biopsies. Research biopsies were divided into two groups: biopsies performed as stand‐alone procedures (research purposes only biopsy, RPOB) or performed during a clinically indicated biopsy (additional pass biopsy, APB). Factors analyzed included biopsy timing, biopsy site, sociodemographic information and information about prior trial participation. Univariate and multivariable analyses were conducted using random‐effects logistic regression. Results: One hundred and sixty‐five patients with cancer (40 melanoma, 37 colorectal, 32 breast, 30 lung, 26 prostate) completed the questionnaire. Patients with melanoma demonstrated the greatest willingness to consider a research biopsy compared to patients with other cancer types ( P  < 0.05). Patients' ethnicity, time since previous biopsies, time since metastatic diagnosis, and previous trial enrolment were all statistically significant for willingness to consider a research biopsy on univariate analysis. When adjusting for statistically significant variables on univariate analysis, the odds of patients considering APBs were 14.6 times greater than RPOBs ( P  < 0.0001). Patients were also more willing to consider having blood or skin taken for research purposes ( P  < 0.0001 ) compared to liver and bone biopsies. Conclusions: Patients with cancer show a greater willingness to consider APBs compared to RPOBs, and biopsies performed at less invasive body sites. There are differences in the attitudes of patients with different cancers towards research biopsies. Further research addressing motivations and barriers to research biopsies should be considered to increase the availability of this important resource.